Nilai-nilai Pendidikan Islam dalam Tari Mesekat Suku Alas di Aceh Tenggara - Gunawan, Mhd Alfat; Ritonga, Asnil Aidah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Islamic education is not only obtained through formal learning. However, Islamic education can be found in cultural practices and traditions that have Islamic values. The Alas tribe is the majority tribe inhabiting Southeast Aceh Regency which has cultural practices and traditions in accordance with Islamic law. The Alas tribe has a Mesekat dance that contains Islamic educational values. However, the Mesekat dance is rarely recognized by the wider community, even the most sad Mesekat dance is not known by some Alas tribe communities themselves. This study aims to introduce Mesekat dance to the wider community and reveal the value of Islamic education contained in the Mesekat dance of the Alas tribe so that it can be an input in Islamic education. This study uses qualitative methods with an ethnographic approach. In collecting data, researchers conduct interviews, observations, literature studies, and documentation. To analyze the data using the opinions of Miles and Huberman. The value of creed, the value of worship, moral values, and social values known as the value of Islamic education are found in the Mesekat Tari Suku Alas, these values are obtained through movements and verses sung by dancers. There is a distinctive value in Islamic education so the Mesekat dance must be preserved and developed to be an input material for Islamic education and useful for the world of education in the future.